Wood finishing: materials used / Lizawati Mohamad Nor - Mohamad Nor, Lizawati (2005)
Wood finishing more specifically on furniture making is a last treatment that we put on wood surface based on artwork and science. Then, the combination both of them will apply in surface layer with three terms of clear, moderate clear and not clear, to show the real wood beauty from finishing. At the same time, it can also make the wood surface more durable from weather; handicap, chemical components and it will increase the value of characteristics in furniture design. To get great finishing, we need to think about materials to be used first because right materials chosen will affect the result in the end of finishing operation. However, we need to have support from finishing techniques that we use because this reason can help us to know the right equipment that we need to use. So, here we can conclude that, we can achieve perfect finishing if we follow the finishing steps besides the experience from workmanship.